Neuroinflammation in Parkinson’s disease: focus on the relationship between miRNAs and microglia - Ke Xu; Yuan Li; Yan Zhou; Yu Zhang; Yue Shi; Chengguang Zhang; Yan Bai; Shun Wang (Frontiers in Cellular Neuroscience, 2024)
Parkinson’s disease (PD) is a prevalent neurodegenerative disorder that affects the central nervous system (CNS). Neuroinflammation is a crucial factor in the pathological advancement of PD. PD is characterized by the presence of activated microglia and increased levels of proinflammatory factors, which play a crucial role in its pathology. During the immune response of PD, microglia regulation is significantly influenced by microRNA (miRNA). The excessive activation of microglia, persistent neuroinflammation, and abnormal polarization of macrophages in the brain can be attributed to the dysregulation of certain miRNAs. Additionally, there are miRNAs that possess the ability to inhibit neuroinflammation. miRNAs, which are small non-coding epigenetic regulators, have the ability to modulate microglial activity in both normal and abnormal conditions. They also have a significant impact on promoting communication between neurons and microglia.